INTERAKSI SUAMI-ISTRI, INTERAKSI ORANG TUA-ANAK, INTERAKSI TEMAN SEBAYA, DAN RESILIENSI REMAJA - Yane Ardian Rachman (Jurnal Ilmu Keluarga dan Konsumen, 2020)
The teenager is a vulnerable phase that needs resilience to optimize their development. This study aimed to determine the influence of husband-wife interaction, parent-child interaction, and the peer interaction on teenager’s resilience. The study was conducted in four vocational and nonvocational high schools (state and private high schools and vocational schools), in the city of Bogor, West Java. Schools were selected purposively. Respondents were 240 mothers and 240 teenagers from grade X who had intact families and lived with their parents. Data analysis used descriptive analysis and inferential analysis (independent sample t-test and multiple linear regression test). The results show that boys tend to have a higher conflict with peers while girls feel closer to peers. Moreover, boys have higher resilience than girls. The teenagers from nonvocational schools have higher resilience than ones from vocational schools. Parent-child interaction and peer interaction have a positive influence on teenager’s resilience. Therefore, parents are expected to improve the quality of interaction in the family and provide encouragement for teens to choose good friends.